2022
DOI: 10.1109/jphot.2022.3206619
|View full text |Cite
|
Sign up to set email alerts
|

Penalties From 2D Grating Coupler Induced Polarization Crosstalk in Silicon Photonic Coherent Transceivers

Abstract: Silicon photonic two-dimensional grating couplers for C-and O-band dual-polarization coherent transceivers are analyzed with respect to their polarization splitting/combining performance. Due to scattered light in the grating's plane, a linear cross-polarization results. The latter is responsible for a limited polarization split ratio and a polarizations' non-orthogonality. The impact of these two quantities is evaluated by system-level simulations with regard to OSNR penalties in coherent systems. For both C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The grating couplers used in our first generation cROSAs comprise circular perturbing elements. For this kind of 2D-GRC, it is known that low polarization crosstalk occurs in a limited wavelength range [16]. This is sufficient to achieve excellent results at a fixed wavelength, as demonstrated in the previous sections.…”
Section: Future Optimizationmentioning
confidence: 67%
See 3 more Smart Citations
“…The grating couplers used in our first generation cROSAs comprise circular perturbing elements. For this kind of 2D-GRC, it is known that low polarization crosstalk occurs in a limited wavelength range [16]. This is sufficient to achieve excellent results at a fixed wavelength, as demonstrated in the previous sections.…”
Section: Future Optimizationmentioning
confidence: 67%
“…In commercial coherent transceivers, the two orthogonally transmitted signals are de-multiplexed in the DSP unit, but polarization crosstalk has to be kept small as to minimize associated penalties [16], [19]. To verify sufficiently low polarization crosstalk of the cROSA, we employ the following routine, indicated in Fig.…”
Section: B Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that this effect scales with the grating's perturbation strength, leading thus to coupling efficiency limitations. The related polarization crosstalk was observed in experiments [4] and it was shown that it is associated with a loss of polarization orthogonality [5]. To address the issue of cross-polarization, its physical background was investigated [6].…”
Section: D Grating Couplers For Improved Polarization Handlingmentioning
confidence: 99%